Penerapan Teknologi Tepat Guna pada Proses Produksi untuk Meningkatkan Kualitas dan Kuantitas Produk Kipang Kacang - Novi Safriani; Nida El Husna; Yusriana Yusriana; Sri Hartuti; Sri Haryani (Jurnal Pemberdayaan Masyarakat Universitas Al Azhar Indonesia, 2026)
Kipang kacang, a traditional Indonesian snack, is widely produced by home industries in Aceh, one of which is “UMKM Kranciis Snack”, the partner in this community service activity. The production of kipang kacang is carried out simply with limited equipment, resulting in a production process that is less effective and efficient, as well as suboptimal product quality and quantity. Therefore, this community service activity aims to improve the quality and quantity of kipang kacang products through the application of Appropriate Technology (AT) in the production process, thereby increasing the partner’s income and standard of living. The implementation methods include educational outreach, technology application in the form of automatic peanut chopper, automatic peanut roaster, kipang mold, dough pressing roller, and production table, as well as technical guidance. The results show that the application of AT in the kipang kacang production process has made production more effective and efficient in terms of time and cost. In addition, both the quantity and quality of the kipang kacang products have improved. The increase in quantity is indicated by a rise in the number of products produced (approximately 80%), while the improvement in quality can be seen from the evenly roasted peanuts, crisper and more uniform kipang texture, and better product hygiene.